Optimalisasi Strategi Pemasaran Bagi Pelaku UMKM Guna Mendukung Pertumbuhan Ekonomi Kreatif - Widya Aulia Siregar; Riyan Pradesyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a major pillar of the national economy, but Rengginang MSMEs in Dolok Kahean Village face challenges adapting to the digital era, characterized by limited market reach through traditional methods and minimal product exposure due to not utilizing digital media. In fact, a digital presence is crucial for achieving positive benefits such as higher income. The main objective of this community service is to provide intensive assistance in implementing digital marketing strategies for Rengginang MSMEs. The implementation method is based on the principle of Participation with a Participatory Action Research (PAR) approach. Concrete actions include intensive Capacity Building Training on digital marketing fundamentals, branding strategies, and product photography techniques, followed by direct assistance in creating and managing social media accounts. The results of the community service demonstrate the successful transformation of Rengginang MSMEs into digitally literate MSMEs. Key achievements include increasing partner digital capacity, activating new digital marketing channels, and strengthening product visual branding. Evaluation through FGDs confirms that this implementation triggers a significant expansion of market reach beyond village boundaries and increased consumer awareness. The conclusion confirms that intensive mentoring is a vital strategy to bridge the digital divide at the village level, thereby effectively supporting the development of the local creative economy and accelerating economic growth.